The World Cup of Economics Journals: A Ranking by a Tournament Method - László Á. Kóczy; Martin Strobel (Hungarian Academy of Sciences, Institute of Economics, 2010)
A ranking of journals is manipulable if a particular journal's position can be improved by making additional citations to other journals. We introduce a simple ranking method that is not manipulable and is invariant to citation intensities, journal scaling and article-splitting. The ranking of economics journals is presented and is compared to rankings by alternative methods in the recent years.
Keywords: A1; C8; D72; Y1; 330; journal ranking; incomplete tournaments; manipulation; invariance; scientometrics; Fachzeitschrift; Ranking-Verfahren; Bibliometrie; Extensives Spiel; Wirtschaftswissenschaft